2016
DOI: 10.1016/j.alcohol.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use by urban bicyclists is associated with more severe injury, greater hospital resource use, and higher mortality

Abstract: Alcohol use is a risk factor for severe injury in pedestrians struck by motor vehicles. Our objective was to investigate alcohol use by bicyclists and its effects on riding behaviors, medical management, injury severity, and mortality within a congested urban setting. A hospital-based, observational study of injured bicyclists presenting to a Level I regional trauma center in New York City was conducted. Data were collected prospectively from 2012 to 2014 by interviewing all bicyclists presenting within 24 h o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 28 publications
5
25
2
Order By: Relevance
“…Of the sober cyclists, however, 20% were provably wearing a helmet. Similar results have been presented previously [4,21,22]. According to a recent metaanalysis of 40 studies with data on more than 64,000 injured cyclists [23], the helmet use of cyclists involved in an accident or fall was associated with an odds reduction for head injury (OR = 0.49, 95% CI: 0.42-0.57), serious head injury (OR = 0.31, 95% CI: 0.25-0.37), facial injury (OR = 0.67, 95% CI: 0.56-0.81) and fatal head injury (OR = 0.35, 95% CI: 0.14-0.88) [23].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Of the sober cyclists, however, 20% were provably wearing a helmet. Similar results have been presented previously [4,21,22]. According to a recent metaanalysis of 40 studies with data on more than 64,000 injured cyclists [23], the helmet use of cyclists involved in an accident or fall was associated with an odds reduction for head injury (OR = 0.49, 95% CI: 0.42-0.57), serious head injury (OR = 0.31, 95% CI: 0.25-0.37), facial injury (OR = 0.67, 95% CI: 0.56-0.81) and fatal head injury (OR = 0.35, 95% CI: 0.14-0.88) [23].…”
Section: Discussionsupporting
confidence: 91%
“…However, in a study from Tokyo, Japan (minor bicycle accidents involving 217 individuals aged !20 years, treated in ED), alcohol intoxication was independently associated with higher medical costs [2]. Two similar results from Arizona and New York indicated that the alcohol-positive cyclists were more seriously injured and their healthcare costs were higher than those of the sober cyclists [5,21].…”
Section: Discussionmentioning
confidence: 86%
“…Some countries, such as Brazil (Gjerde et al, 2015) have contributed with a large number of research studies (Pechansky et al, 2010) but for most countries the evidence is scattered and not comparable. Most importantly, there is a paucity of evidence on the presence of alcohol in RTIs among pedestrians and non-driver riders, who are important victims of RTIs(du Plessis et al, 2016; Forson et al, 2016; Maximus et al, 2016; Senserrick et al, 2014; Sethi et al, 2016; Waller et al, 1986). …”
Section: Introductionmentioning
confidence: 99%
“…Only 8.2% of intoxicated bicyclists wore helmets, whereas the helmet use rate among sober bicyclists was 53.5%. This is a finding that has previously been uncovered using data from medical records in studies by Sethi et al (2016) and Andersson and Bunketorp (2002) who found intoxicated cyclists less likely to wear helmets and more likely to be severely injured (Sethi et al, 2016) or obtain head and face injuries (Andersson and Bunketorp, 2002). Although this model did not find helmet use to be a factor in injury severity, possibly due to the high percentage of missing data, the low helmet use among intoxicated bicyclists may be in part attributing to the increased probability of severe injuries predicted by this variable.…”
Section: Bicyclist Drinkingsupporting
confidence: 57%
“…Alcohol consumption has also been shown to increase severe injuries. Sethi et al (2016) found that alcohol use in urban bicyclists was inversely correlated with helmet use and associated with more severe injuries and greater mortalities. Andersson and Bunketorp (2002) found that intoxicated cyclists less often wore helmets and were at a greater risk of head and face injuries.…”
Section: Previous Literaturementioning
confidence: 97%